Vitamin D protects dopaminergic neurons against neuroinflammation and oxidative stress in hemiparkinsonian rats - Ludmila A R Lima; Maria Janice P Lopes; Roberta O Costa; Francisco Arnaldo V Lima; Kelly Rose T Neves; Iana B F Calou; Geanne M Andrade; Glauce S B Viana (Journal of Neuroinflammation, 2018)
Abstract Background The deficiency in 1α, 25-dihydroxyvitamin D3 (VD3) seems to increase the risk for neurodegenerative pathologies, including Parkinson’s disease (PD). The majority of its actions are mediated by the transcription factor, VD3 receptor (VD3R). Methods The neuroprotective effects of VD3 were investigated on a PD model. Male Wistar rats were divided into the following groups: sham-operated (SO), 6-OHDA-lesioned (non-treated), and 6-OHDA-lesioned and treated with VD3 (7 days before the lesion, pre-treatment or for 14 days after the 6-OHDA striatal lesion, post-treatment). Afterwards, the animals were subjected to behavioral tests and euthanized for striatal neurochemical and immunohistochemical assays. The data were analyzed by ANOVA and the Tukey test and considered significant for p < 0.05. Results We showed that pre- or post-treatments with VD3 reversed behavioral changes and improved the decreased DA contents of the 6-OHDA group. In addition, VD3 reduced the oxidative stress, increased (TH and DAT), and reduced (TNF-alpha) immunostainings in the lesioned striata. While significant decreases in VD3R immunoreactivity were observed after the 6-OHDA lesion, these changes were blocked after VD3 pre- or post-treatments. We showed that VD3 offers neuroprotection, decreasing behavioral changes, DA depletion, and oxidative stress. In addition, it reverses partially or completely TH, DAT, TNF-alpha, and VD3R decreases of immunoreactivities in the non-treated 6-OHDA group. Conclusions Taken together, VD3 effects could result from its anti-inflammatory and antioxidant actions and from its actions on VD3R. These findings should stimulate translational research towards the VD3 potential for prevention or treatment of neurodegenerative diseases, as PD.